Model of integrated mental health video consultations for people with depression or anxiety in primary care (PROVIDE-C): assessor masked, multicentre, randomised controlled trial - Haun, Markus W.; Tönnies, Justus; Hartmann, Mechthild; Wildenauer, Alina; Wensing, Michel; Szecsenyi, Joachim; Feißt, Manuel; Pohl, Moritz; Vomhof, Markus; Icks, Andrea; Friederich, Hans-Christoph (The BMJ, 2024)
Objective To evaluate whether an integrated mental health video consultation approach (PROVIDE model) can improve symptoms compared with usual care in adults with depression and anxiety disorders attending primary care. - Design Assessor masked, multicentre, randomised controlled trial (PROVIDE-C). - Setting In 29 primary care practices in Germany, working remotely online from one trial hub. - Participants 376 adults (18-81 years) who presented to their general practitioner (GP) with depression or anxiety, or both. - Intervention Participants were randomised (1:1) to receive the PROVIDE model (n=187) or usual care (n=189). Usual care was provided by GPs through interventions such as brief counselling and psychotropic medication prescriptions and may or may not have included referrals to mental health specialists. The PROVIDE model comprised transdiagnostic treatment provided through five real-time video sessions between the patient at the primary care practice and a mental health specialist at an offsite location. - Main outcome measures The primary outcome was the absolute change in the mean severity of depressive and anxiety symptoms measured using the patient health questionnaire anxiety and depression scale (PHQ-ADS) at six months, in the intention-to-treat population. Secondary outcomes, measured at six and 12 months, included PHQ-ADS subscores, psychological distress related to somatic symptoms, recovery, health related quality of life, quality and patient centredness of chronic illness care, and adverse events. - Results Between 24 March 2020 and 23 November 2021, 376 patients were randomised into treatment groups. Mean age was 45 years (standard deviation (SD) 14), 63% of the participants were female, and mean PHQ-ADS-score was 26 points (SD 7.6). Compared with usual care, the PROVIDE intervention led to improvements in severity of depressive and anxiety symptom (adjusted mean change difference in the PHQ-ADS score −2.4 points (95% confidence interval −4.5 to −0.4), P=0.02) at six months. The effects were sustained at 12 months (−2.9 (−5.0 to −0.7), P<0.01). No serious adverse events were reported in either group. - Conclusions Through relatively low intensity treatment, the PROVIDE model led to a decrease in depressive and anxiety symptoms with small effects in the short and long term. Depression and anxiety disorders are prevalent and therefore the small effect might cumulatively impact on population health in this population. - Trial registration ClinicalTrials.gov NCT04316572.